The relation of close friends to cognitive performance in old age: the mediating role of leisure activities. (1st June 2018) - Ihle, Andreas; Oris, Michel; Baeriswyl, Marie; Kliegel, Matthias
ABSTRACT: Background: From a conceptual point of view, close friends are an important resource for promoting activity engagement in old age. Leisure activity engagement in turn is a key predictor of cognitive performance. Empirically, it remains unclear so far whether leisure activity engagement mediates between having close friends on the one hand and cognitive performance on the other, which we investigated in a large sample of older adults. Methods: We assessed cognitive performance (Mill Hill vocabulary scale and Trail Making Test (TMT) parts A and B) in 2, 812 older adults. Participants reported information on leisure activity engagement and close friends. Results: A larger number of leisure activities and a larger number of close friends were significantly related to better cognitive performance in the Mill Hill vocabulary scale and TMT parts A and B. A larger number of close friends were significantly related to a larger number of leisure activities. The number of leisure activities mediated more than half of the relation of the number of close friends to performance in all three cognitive measures. Conclusions: Having close friends may be helpful to stimulate and promote activity participation in old age. By enhancing individuals' cognitive reserve, this may finally preserve their cognitive performance level in old age.